Analysis of Feasibility Indicators of Two Wheel Engine Oil Using Light Sensor (LDR) - Ike Yuni Wulandari; Yoana Nurul Asri (Journal of Applied Sciences and Advanced Technology, 2020)
The oil feasibility measurement tool to determine the viscosity level contained in a two-wheeled vehicle using a light sensor (LDR) has been designed and implemented. Testing through five oil brands with homogeneous specifications that are generally used by two-wheeled vehicles. The manufacture of this tool uses three integrated systems in one method, namely: input via the LCD and laser sensors, the process system by the microprocessor in the form of Arduino, and the output in the form of an LCD final display. These three systems are connected through the gear box block mechanical system. The results are converted to the electrical resistance value that appears on the indicator. The set point in the form of the range of electrical resistance was obtained through experiments from the five new oil brands. Furthermore, the wheels of the Gear Box are rotated to produce a value in the form of RPM. From these five types of oil, data is obtained that the gear box which rotates in a duration of twenty minutes with a minimum speed of 210 RPM and a maximum speed of 720 RPM indicates that the quality of the oil is in a good category